Study of thermal degradation products of poly [2-(3-mesityl-3-methylcyclobutyl)-2-ketoethylmetracrylate] - Ilter, Zulfiye; Kaya, Ismet; Erol, Ibrahim; Yildiz, H. Ibrahim; Ahmedzade, Misir (Freund Publishing House Ltd, 2007)
The thermal degradation of poly [2-(3-mesityl-3-methylcyclobutyl)-2-ketoethylmethacrylate] (PMKEMA) has been studied using a system consisting of a degradation tube, with a condenser for product collection, a gas-phase Infrared (IR) cell and a rotary pump. The investigation of the nature of the evolved products has been supplemented by studies of structural changes in the degrading polymer by Fourier Transform Infrared (FT-IR) technique. Changes have been investigated under programmed heating at 10 degrees C/min from room temperature to 500 degrees C. The product identification investigations were done by using FT-IR, H-1 and C-13-Nuclear Magnetic Resonance (H-1-C-13-NMR) and Gas Chromatography-Mass Spectrometer (GC-MS) techniques. The depolymerization of the main reaction is essential in thermal degradation of the PMKEMA. The degradation produces anhydride ring structures in the chain at temperatures up to about 300 degrees C. The cleaving of ketone, aldehyde, and mesitylene compounds from side chains of the polymers is a common reaction for the polymers. A mechanism of degradation showing the formation of some of these products is discussed.
Keywords: poly [2-(3-mesityl-3-methylcyclobutyl)-2-ketoethylmethacrylate]; GC-MS; thermal degradation